Diatom-based reconstruction of the Holocene evolution of Lake St Lucia, South Africa - Gomes, Megan (My University, 2016)
Coastal waterbodies along the east coast of southern Africa evolved from fluvial origins that were slowly drowned by rising sea levels during the Holocene. The accumulation of sediment in these systems is relatively undisturbed, providing ideal sites from which longer term observations of palaeo-climatic variability over most of the Holocene period can be made. Lake St. Lucia, on the north coast of KwaZulu- Natal, is the largest estuarine lagoon in Africa and is widely regarded as one of the most important shallow water systems globally. Despite the importance of this system, little is currently know about the processes driving the long-term evolution of the lake. This study aimed to reconstruct the hydrological changes associated with the Holocene evolution of Lake St. Lucia using fossil diatoms. Analyses were performed on two sediment cores from the North Lake (15.6 m) and False Bay (15.9 m) basins of Lake St. Lucia. Age models, each based on eight radiocarbon dates, revealed continuous sedimentary records covering ~8300 cal. yr BP. A total of 150 samples were examined resulting in a total of 113 species recorded which were used to infer changes in environmental conditions based on their reported ecological preferences.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. March 2016
Keywords: Diatoms; South Africa--Lake St Lucia--Holocene